2013
DOI: 10.1590/s0080-62342013000200012
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de pacientes com câncer hematológico em tratamento quimioterápico

Abstract: Estudo descritivo, transversal desenvolvido com objetivo de associar aspectos socio demográficos e clínicos aos domínios de qualidade de vida relacionada à saúde (QVRS), para avaliar pacientes onco-hematológicos submetidos à quimioterapia. Na coleta de dados utilizou-se um instrumento sociodemográfico e clínico e o European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC) QLQ-C-30. A amostra foi constituída de 32 pacientes, sendo oito (25%) com diagnóstico de linfoma de H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0
35

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(57 citation statements)
references
References 14 publications
3
18
0
35
Order By: Relevance
“…However, a review performed in Germany with the main QOL studies using the QLQ-C30 to evaluate the pre-and post-HSCT (11) , and another review performed in Chicago (USA) that compared the QOL of patients undergoing autologous and allogeneic HSCT in 105 participants with cancer, showed the patients' age was between 40 and 50 years (12) , which differs from the present study findings. The marital status and number of children in this study corroborate data found in national and international literature, i.e., patients with hematological malignancies are married or in a common-law marriage and have one to three children (12)(13)(14)(15)(16) . In a study on the bond between cancer patients and their families, it was observed that the main companions of patients with neoplasia are children, spouses and parents, and family involvement is critical during the disease process.…”
Section: Discussionsupporting
confidence: 87%
“…However, a review performed in Germany with the main QOL studies using the QLQ-C30 to evaluate the pre-and post-HSCT (11) , and another review performed in Chicago (USA) that compared the QOL of patients undergoing autologous and allogeneic HSCT in 105 participants with cancer, showed the patients' age was between 40 and 50 years (12) , which differs from the present study findings. The marital status and number of children in this study corroborate data found in national and international literature, i.e., patients with hematological malignancies are married or in a common-law marriage and have one to three children (12)(13)(14)(15)(16) . In a study on the bond between cancer patients and their families, it was observed that the main companions of patients with neoplasia are children, spouses and parents, and family involvement is critical during the disease process.…”
Section: Discussionsupporting
confidence: 87%
“…The data demonstrates a demographic behavior presented in other studies, in which the number of cancer in women is greater in relation to men. 6,[17][18][19] In the United States, a study carried out with the participation of 45,541 people, also highlighted the highest occurrence in women, represented by a quantitative of 29,822. 20 Regarding the participants' age, it was found that 60.7% were elderly, with a higher percentage of patients in the 60-69 age group.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-two participants were involved and statistically significant results were also found for the schooling variable in relation to the Social function, with a better assessment for those with a higher schooling level. 18 Recognized as socioeconomic factors, education and income promote interactions and influences health, as an individual's purchasing power has a direct effect on this person's education and, consequently, on this person's health. The person with a higher schooling level is likely to get a better salary and thus can better meet the health demands: access to health services, medical appointments, medications, health insurance, good living conditions, among others.…”
mentioning
confidence: 99%
“…This might be related to the adverse reactions of chemotherapy and less side effects of radiotherapy for blood cancer patients, which depend on the dose of the treatment, the part of the body being exposed to radiation, the length of radiation period and other factors. A study in Brazil (Andrade, Sawada & Barichello, 2013), revealed that the emotional and cognitive side effects of chemotherapy negatively influenced the QoL of hematologic oncology patients.…”
Section: Discussionmentioning
confidence: 99%